(untitled) (Andamios, Revista de Investigación Social, 2009)
This is a brief essay about the relations between facts, ideas, and focusses that have marked various tendencies in Mexican political science in the last thirty years. The central argument is that these works have taken shape in the “epistemological communities” that comprise contemporary political science in Mexico. Starting from a revision of literature produced from 1980 to 2008, we propose a general, preliminary map of the orientations, agendas, problems and methods of investigation that characterize Mexican political analysis of recent years